(3cJGH aj GdCOHs
(3ChdgG (B:s
(3GdMeO ddg GdPj cJH Ydi faSg GdQMeI dCgd WGYJg, haQV GdRdaI def CaVi ajg eWGjG GSJWGYJg, s
(3BNQgG (B:s
(3eG GJUdJ GdCjGe HGddjGdj, hJRjf GdOgQ ef efGbHg HaGNQ GddBdj s
(3Vef eLehY , JQJjHgG (B: (3ef U (B11 - (3U(B58s
(3GdfSNI HgG MhGTs
(3jMJhj Ydi eNJGQGJ aj GdTYQ hafhfgs
(3ebOe Edi CejQ GdLjhT CHj YHOGddg eMeO GdCeQjs
(3hYdi gGeTgG ebGHdGJs
(3hHgG VHW s
(3bQf GdfSN (B:s
Keywords: (3GdCOHs